Public opinion analysis on social media about the establishment of Indonesia's New Capital City - Kadewandana, Donie; Cahyadiputra, Angga (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
One of the policies of President Joko Widodo's administration that is currently receiving various opinions is the issue of moving the Indonesian capital city from DKI Jakarta Province to East Kalimantan Province, to be precise, in Kutai Kartananegara Regency, which uses the name of the new capital city, Ibu Kota Nusantara (IKN). President Joko Widodo officially announced the transfer of the national capital on Monday, August 26, 2019, at the state palace. There were a variety of opinions regarding the capital city relocation policy. This study aims to find out the sentiment of public opinion regarding the move of the Indonesian capital to Kalimantan based on the hashtag #MovingCapitalCity on Twitter social media (now called